2019
DOI: 10.1111/febs.14929
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive map of human elastin cross‐linking during elastogenesis

Abstract: Elastin is an essential structural protein in the extracellular matrix of vertebrates. It is the core component of elastic fibers, which enable connective tissues such as those of the skin, lungs or blood vessels to stretch and recoil. This function is provided by elastin's exceptional properties, which mainly derive from a unique covalent cross‐linking between hydrophilic lysine‐rich motifs of units of the monomeric precursor tropoelastin. To date, elastin's cross‐linking is poorly investigated. Here, we puri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
51
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 34 publications
(53 citation statements)
references
References 73 publications
(151 reference statements)
1
51
1
Order By: Relevance
“…In our recent studies of bovine and human elastin, we sequenced several tetrafunctionally cross‐linked peptides, in which all assignable peptide strands were derived from KA domains. In human elastin, the single‐Lys cross‐linking domain 14 was found to be involved in DES/IDES formation together with two other KA domains, which is in contrast to the previously described assumptions that postulated the involvement of only two KA domains in DES/IDES formation …”
Section: Lysyl Oxidase‐mediated Cross‐linkingcontrasting
confidence: 96%
See 4 more Smart Citations
“…In our recent studies of bovine and human elastin, we sequenced several tetrafunctionally cross‐linked peptides, in which all assignable peptide strands were derived from KA domains. In human elastin, the single‐Lys cross‐linking domain 14 was found to be involved in DES/IDES formation together with two other KA domains, which is in contrast to the previously described assumptions that postulated the involvement of only two KA domains in DES/IDES formation …”
Section: Lysyl Oxidase‐mediated Cross‐linkingcontrasting
confidence: 96%
“…In conclusion, recent studies have shown that distinct Lys residues can be involved in different types of cross‐links or even remain unaltered . One of the many examples for this diversity is Lys‐104 in domain 6 of human elastin (see Figure , left half).…”
Section: Lysyl Oxidase‐mediated Cross‐linkingmentioning
confidence: 88%
See 3 more Smart Citations